Budaya Sekolah Sebagai Hidden Curriculum Pembentuk Karakter Lulusan Lembaga Pendidikan Islam - Binti Nasukah (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2017)
The criticism addressed to Islamic Education Institutions (IEI) attribute to its incompetence to overcome the bad habit in this country such as corruption, collusion and nepotism, raise the need of IEI to realize the existence of hidden curriculum. It is side effect  of education when formal curriculum to be implemented, through school culture. Hidden curriculum embedded in school culture that participate in creating student’s character. Using literature studies, this article try to give undertstanding about the importance of hidden curriculum, including its existence and sources, and give recommendation for IEI’s administrators to evaluate the aspects contributing to school culture and impacting the hidden curriculum.  It is hoped that realizing the existence of hidden curriculum will help IEI to evaluate many posibilities that cause unexpected output of education.     Keywords: hidden curriculum, school culture, Islamic education institutions